The effect of skin orientation on biomechanical properties / Nor Fazli Adull Manan and Jamaluddin Mahmud - Adull Manan, Nor Fazli; Mahmud, Jamaluddin (Faculty of Mechanical Engineering & UiTM Press, 2015)
Skin technology has become a world interest recently and further investigations could improve the current application of skin and leather. Aligning to this, a biomechanical analysis of animal skin is carried out, where the sheepskins are investigated thoroughly using uniaxial tensile tests. The main aim of this study is to compare the biomechanical properties of sheepskin in means of hair effect and orientation layout between horizontal and vertical orientation. The testing specimens are taken from the fresh slaughtered Boer sheepskin and they are prepared into four categories; horizontal (unshaved), horizontal (shaved), vertical (unshaved) and vertical (shaved) according to ASTM International Standard test method for tensile strength of leather (D2209). As a result, the characterisation techniques show that the Ogden s coefficient, μ and Ogden s exponent, α, are 0.369 (MPa) and 7.604 respectively for horizontal (unshaved). However, μ and a for horizontal (shaved) are 0.512 (MPa) and 8.930. In contrast, the value of μ and a for vertical (unshaved) are 0.444 (MPa) and 9.928 and for vertical (shaved) are 0.539 (MPa) and 10.617. This study has contributed to the knowledge of biomechanics especially biomechanical properties of sheepskin. This could be useful for future investigation and analysis of softtissues, hyperelastic modeling and animal dermatology.